High molecular weight RNAs and small interfering RNAs induce systemic posttranscriptional gene silencing in plants - Klahre, Ulrich (The National Academy of Sciences, 2002)
Posttranscriptional gene silencing (PTGS) in transgenic plants is an epigenetic form of RNA degradation related to PTGS and RNA interference (RNAi) in fungi and animals. Evidence suggests that transgene loci and RNA viruses can generate double-stranded RNAs similar in sequence to the transcribed region of target genes, which then undergo endonucleolytic cleavage to generate small interfering RNAs (siRNA) that promote degradation of cognate RNAs. The silent state in transgenic plants and in Caenorhabditis elegans can spread systemically, implying that mobile silencing signals exist. Neither the chemical nature of these signals nor their exact source in the PTGS pathway is known. Here, we use a positive marker system and real-time monitoring of green fluorescent protein expression to show that large sense, antisense, and double-stranded RNAs as well as double-stranded siRNAs delivered biolistically into plant cells trigger silencing capable of spreading locally and systemically. Systemically silenced leaves show greatly reduced levels of target RNA and accumulate siRNAs, confirming that RNA can induce systemic PTGS. The induced siRNAs represent parts of the target RNA that are outside of the region of homology with the triggering siRNA. Our results imply that siRNAs themselves or intermediates induced by siRNAs could comprise silencing signals and that these signals induce self-amplifying production of siRNAs.